2021
DOI: 10.3390/ijerph18083946
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between College Students’ Sedentary Behavior, Sleep Quality, and Body Mass Index

Abstract: Purpose: Sedentary behavior (SB), sleep efficiency (SE), sleep duration (SD), and body mass index (BMI) are crucial determinants of an individual’s health. However, empirical evidence regarding associations between these factors in young adults living in China remains unknown. Therefore, the purpose of this study was to examine the relationships between accelerometer-measured SB, SE, SD, and BMI in Chinese college students. Methods: Two-hundred and twenty college students (115 females, Meanage = 20.29 years, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(66 reference statements)
0
4
0
1
Order By: Relevance
“…These findings are consistent with other findings among young adults demonstrating that there is an inverse relationship between SB and sleep efficiency. 68 Likewise, a growing body of research has demonstrated that increased PA levels improve adults’ sleep quality. Thus, the concurrent decreases in SB and increases in PA among the intervention group—especially that of moderate- and vigorous-intensities—lead to significantly improved sleep efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other findings among young adults demonstrating that there is an inverse relationship between SB and sleep efficiency. 68 Likewise, a growing body of research has demonstrated that increased PA levels improve adults’ sleep quality. Thus, the concurrent decreases in SB and increases in PA among the intervention group—especially that of moderate- and vigorous-intensities—lead to significantly improved sleep efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous evidence supports the direction of this association, attributing to physical activity a predictive effect for better sleep quality 18 . Although sedentary behavior is associated with both variables of interest 23 , 24 , information on this behavior was not available for the present study. Although accelerometers and pedometers are used as objective measures to assess this practice 25 , questionnaires are commonly employed in epidemiological studies 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was demonstrated in adult subjects that poorer sleep efficiency is related to higher fat mass [24]. In addition, a recent study reported that BMI negatively predicted sleep duration and sleep efficiency in Chinese young adults [25]. Sweatt et al [26] showed that lower sleep quality is associated with elevated visceral adipose tissue, and poor sleep quality was positively associated with fat mass percentage in Spanish subjects [27].…”
Section: Discussionmentioning
confidence: 98%